The Issue of the Ethnic Structure of the Population of The Upper Sura and Moksha Regions in the Golden Horde Period - Vladimir Al. Vinnichek; Karina M. Vinnichek; Andrei V. Didyulin (Археология евразийских степей, 2022)
The paper concerns the investigation of the ethnic structure of the population of the Upper Sura and Moksha regions of the 13th – 14th centuries. The analysis and systematization of archaeological materials allowed the authors to draw the following conclusions. The artefacts of the Golden Horde archaeological monuments of the upper Sura and Moksha indicate that the dominant ethnic group in the region was the Mordovians. This is evidenced by lobed sulgams, ring clasps, wire earrings with a multi-faceted weight at the lower end, and iron jewelry. Along with the pagan Mordovians, a significant proportion of the Bolgar population who professed Islam lived in these regions. This is confirmed by a discovered talisman with an Arabic inscription of the name of Allah and a complex of silver jewelry found at Nikolsky ancient village. Artifacts from the Upper Sura and Moksha also indicate an increased influx of the Russian population to the regions in the second half of the 13th – 14th centuries. Slavic ethnomarkers should include Christian relics and individual jewelry items, as well as the discovered pottery typical of Ancient Russia found in the territory of Narovchatsky settlement. Nomadic tribes also left their mark in the upper reaches of the Sura and Moksha.